Oxidative Stress in Muscle Diseases: Current and Future Therapy 2019 - Serra, Andrey (2020)
Increased oxidative stress has important molecular, structural, and functional muscle implications. In pathological conditions, reactive oxygen species (ROS) burst contributes to cellular dysfunction and the progression of muscle diseases. This special issue was designed to advance knowledge in the role of oxidative stress on muscle remodeling, in turn leading to innovative therapeutic approaches in a wide range of muscle diseases. Therefore, this special issue provides recent scientific advancements with researchers and practitioners who work in muscle scope. Articles included in this special issue address the molecular and cellular mechanisms involved in these processes as well as current therapies.